Epidemiological characteristics of dementia and its correlation with multimorbidity among people aged 65 and above - Sijing Zhou; Bangan Luo; Hui Cao; Xi Zhang; Dongxin Wang (Chinese General Practice Journal)
Background: With population aging, the prevalence of dementia is rising annually, alongside a rise in multimorbidity. However, comprehensive surveys on the prevalence of dementia in older population in Hunan Province are limited, and the comorbid relationships between diseases remain unclear. Objective: To comprehensively understand the prevalence of dementia among older people aged 65 years and above in Hunan Province and analyze its comorbidity relationships with 11 common chronic diseases. Methods: From April to May 2021, using stratified multistage sampling, residents aged 65 years and above were randomly surveyed across 30 districts/counties, 60 streets/townships, and 180 community/village committees in Hunan Province. Dementia diagnosis was conducted by neurologists or psychiatrists using the Community Screening Interview for Dementia (CSI-D) or the 8-item dementia questionnaire (AD8), along with the Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA). Additionally, the prevalence of hypertension, cerebrovascular disease, ischemic heart disease, rheumatoid arthritis, intervertebral disc disease, diabetes, gastroenteritis, chronic obstructive pulmonary disease, cholecystitis cholelithiasis, peptic ulcer, and cancer was investigated. Results: Out of the 5,979 individuals sampled, 5,616 completed the survey, with 785 cases (13.98 %) identified with dementia. Comparisons of dementia prevalence among different regions, genders, ages, smoking histories, and chronic disease conditions showed statistically significant differences (P < 0.05). A total of 5,606 sets of chronic disease prevalence data were collected, with hypertension [2,205 (39.33 %)], intervertebral disc disease [553 (9.86 %)], diabetes [526 (9.38 %)], cerebrovascular disease [492 (8.78 %)], and ischemic heart disease [467 (8.33 %)] being the most common. In the dementia group, the most prevalent conditions were hypertension [325 (41.40 %)], cerebrovascular disease [111 (14.14 %)], ischemic heart disease [91 (11.59 %)], rheumatoid arthritis [89 (11.33 %)], and intervertebral disc disease [81 (10.31 %)]. The prevalence rates of dementia among groups with varying numbers of chronic diseases ranged from 11.46 % to 18.26 %, increasing with the number of conditions. Significant differences in dementia prevalence were found in individuals with gastroenteritis, rheumatoid arthritis, cerebrovascular disease, chronic obstructive pulmonary disease, and ischemic heart disease (P < 0.05). Binary logistic regression analysis showed that living in rural areas [OR = 2.048, 95 %CI (1.655, 2.536)], being female [OR = 1.388, 95 %CI (1.163, 1.655)], advanced age [OR = 1.348, 95 %CI (1.270, 1.431)], and suffering from chronic diseases [OR = 1.195, 95 %CI (1.101, 1.297)] were risk factors for dementia in residents aged ≥ 65 (P < 0.05). Regarding medication adherence, 12.79 % (99/774) dementia patients reported difficulties, 6.59 % (51/774) needed assistance, and 2.97 % (23/774) were unable to manage independently. Conclusion: The prevalence of dementia among residents aged ≥ 65 in Hunan Province is influenced by the number of chronic diseases and varies with different conditions. The self-care abilities and family care burdens of dementia patients with comorbidities should attract widespread attention from all of the society. These findings aim to provide recommendations for the development of prevention and control policies for dementia and related comorbidities in Hunan Province.